Теоретичні аспекти формування обліково-аналітичного забезпечення стратегічного розвитку підприємств - Левик, І. С.; Чубай, В. М.; Levyk, I. S.; Chubai, V. M. (Видавництво Львівської політехніки, 2017)
Розглянуто та проаналізовано основні наукові підходи до трактування понять «обліково-аналітична система», «обліково-аналітичне забезпечення», їхній взаємозв’язок із системою управління у контексті стратегічного розвитку підприємств. Визначено структуру та взаємозв’язок елементів обліково-аналітичної системи.

Complication of economic environment poses new challenges to the management of domestic enterprises. Attempts to reform the accounting system, the use of borrowed tools and methods of analysis corresponding to international experience led to a decline in the quality of management data, its analysis, as well as the performance of managerial decisions. According to the abovementioned, the urgent task is to resolve issues concerning the development of accounting and analytical systems as a single integrated accounting and analytic enterprise system that will ensure the development of adequate accounting and analytical security to make justified strategic decisions for the development of enterprises and meet other users’ needs for information. The article examines the formation of accounting and analytical security in the context of the strategic development of domestic enterprises. The main approaches to the definition of enterprise development are systematized; its key features are exemplified. Taking into account the fact that domestic enterprises mainly carry out business without a clearly formulated strategy, it is offered to identify strategic goals, quantitative measurements of which will enable to more precisely evaluate the impact of managerial decisions, as strategic guidelines of enterprise development. Having analyzed, summarized and systematized the research work of many scientists, approaches to the interpretation of the concepts of «accounting and analytical system» and «accounting and analytical security» to clear their distinction are considered. It is offered to define accounting and analytical security as the result of the operation of accounting and analytical systems, which is the information of required amount and content. The attention is also paid to the need for the inclusion of modern accounting and analysis systems to the monitoring subsystem to process information about environmental factors that may influence the development of the enterprise. According to the research results organizational forms of accounting and analytical systems, taking into account the distribution of functional responsibilities between departments, are singled out. A process model of accounting and analytical security formation into accounting and analytical system is presented. Subsequent to the research results it is identified that the most appropriate is the formation of accounting and analytical security for specific development directions and alternative strategic decisions on the development in an integrated accounting and analytical system. Since business entities differ in industry classification, scope of activity, type of product, stage of activity life cycle, etc., then during the formation of accounting and analytical security for their strategic development the abovementioned features, which will be the basis of the following studies, should be considered.
Theoretical aspects of accounting and analytical security of enterprise strategic development
Keywords: стратегічний розвиток; обліково-аналітична система; обліково- аналітичне забезпечення; strategic development; accounting and analytical security; accounting and analytical system; 657; 65.012